Wintertime heat flux to the underside of east Antarctic pack ice - Lytle, VI; Robert Massom; Nathaniel Bindoff; Worby, AP; Ian Allison (2000)
In the sea ice zone, there is a delicate balance between the heat loss from the surface of the snow-covered sea ice and the heat supplied to the underside of the ice by the deep ocean. The difference between these two heat fluxes determines the amount of ice growth or melt. In global atmospheric models the ocean heat flux is often prescribed and has been shown to be an important parameter in determining how thick sea ice will grow thermodynamically. Although this ocean heat flux is a critical component in climate models, there are relatively few direct measurements in the Antarctic sea ice region. In this study we use measurements of the temperature gradient through the sea ice and of ice growth during a field experiment to estimate the ocean heat flux in the East Antarctic region around 140° E, 65° S during August 1995. We find an average ocean heat flux of 13.0-14.5 W m-2. This is more than twice the winter values reported in the western Weddell Sea under multiyear sea ice but similar to the 19 W m-2 that has been estimated for the entire Weddell Gyre. During August 1995 the air temperature showed large variations, ranging from near freezing to -30°C. This resulted in the thicker ice floes (50-60 cm) alternating between a no-growth or melting condition and an active ice growth at the base. However, it is likely that the thicker (>60 cm), ridged portions of the floes were continually melting. Copyright 2000 by the American Geophysical Union.